The Amish blacksmith [large type] - Clark, Mindy Starns (Clark, Mindy Starns. Men of Lancaster County series., 2014)
"A tender novel of friendship, love, and the power of trusting God to change hearts and lives set in the close knit Amish community of Lancaster County"--